Penambangan Pasir Ilegal: Studi Kasus Dampak Ekologi Penambangan Pasir Ilegal Pada Desa Sumberasri Nglegok Blitar - Ain Nurahmi; A Zahid (Jurnal Ekologi, Masyarakat dan Sains, 2024)
Abstract: Case on of that research is to show that the effects of fine crackle exploitation are related to the sustainability of the area on Sumbersari Area, Nglegok Region. Where that research intends to elaborate that the effects of fine crackle exploitation are related to the sustainability of the area on Sumbersari Area, Nglegok Region and to respond related to this problem, review use qualitative approach, how to process the data with investigation, interviews, and filing. And the main thing this of the study show that effects of fine crackle exploitation are related to the sustainability of the area on Sumbersari Area, Nglegok Region, Blitar City, which the main thing this provides good effect in the form of increased income for miners and the availability of material in the form of natural sand at affordable prices and order times tend to be faster.